A randomized controlled trial on the effect of VCO in reducing glucose and body weight in post-acute coronary syndrome patients : a pilot study - Sharifah Shafinaz Sh. Abdullah; Chong, Mei Chan; Khatijah Lim Abdullah; Imran Zainal Abidin; Yap, Bee Wah (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aims of this paper were to determine the effect of virgin coconut oil (VCO) on bodyweight and serum glucose level among acute coronary syndrome (ACS) patients. Various clinical trials on animal studies have found that the VCO has many beneficial effects on health. However, there have been limited published human studies on the pharmacological properties of VCO. Investigation on human subjects is extremely required in order to provide more empirical evidence to show the effect of VCO for ACS patients. Randomised single blind study conducted between March 2018 and April 2018. RCT was conducted among 70 ACS patients for 30 days. Participants in group A received their bottles containing 100 pieces of virgin coconut oil soft gels and were required to ingest 10 capsules per day (5 mL/5 gm) and continue routine treatment (diabetic diet and diabetic medication). Group B participants continued receiving routine treatment. Changes in serum fating blood sugar and body weight were identified using a paired t-test and independent t-test. A total of 70 patients participated with ages of 51 years old and older and were mostly male. The serum FBS and body weight of the intervention group that received VCO were reduced about 13.6% on day 30, from the baseline on day 1. They also had body weight reduction of about 2% with p value of less than 0.05. In contrast, the control group that only received routine treatment showed an increment of 12.1% in their serum FBS and had no changes in body weight. These reductions were noted within 30 days of consuming a daily dose of VCO (5 g every day). The properties of lauric acid and antioxidants present in the VCO composition were key players in the reduction of serum glucose levels and body weight. VCO can reduce serum glucose levels and body weight with 5 mL (5 g) of VCO per day for 30 days. Also, VCO may have a positive effect towards the glucose level and other cardiovascular risk factors.